1969
DOI: 10.1017/s0022112069000449
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic balances of dissolved air and heat in natural cavity flows

Abstract: In steady, fully developed and unventilated cavity flows occurring in practice, air (originally dissolved in the water) and heat are diffused through the fluid towards the interface providing a continuous supply of air and vapour to the cavity. This must be balanced by the rate of entrainment of volume of air and vapour away from the cavity in the wake. These equilibria which determine respectively the partial pressure of air within the cavity and the temperature differences involved in the flow are studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 4 publications
2
30
0
1
Order By: Relevance
“…One of the consequences of the balance between the supply of noncondensable gas (air) and its removal by entrainment is the inherent regulation of the partial pressure of the noncondensable gas (air) in the cavity. Brennen (1969) put together a simplified model of these processes and showed that the results for the partial pressure of air were in rough agreement with experimental measurements of that partial pressure. Moreover, there is an analogous balance of heat in which the latent heat removed by the entrainment process must be balanced by the heat diffused to the cavity through the interfacial layer.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…One of the consequences of the balance between the supply of noncondensable gas (air) and its removal by entrainment is the inherent regulation of the partial pressure of the noncondensable gas (air) in the cavity. Brennen (1969) put together a simplified model of these processes and showed that the results for the partial pressure of air were in rough agreement with experimental measurements of that partial pressure. Moreover, there is an analogous balance of heat in which the latent heat removed by the entrainment process must be balanced by the heat diffused to the cavity through the interfacial layer.…”
mentioning
confidence: 72%
“…Instead, a pair of counter-rotating vortices with gas/vapor cores form in the closure region (Cox and Claydon 1956); this type of closure is much steadier and less turbulent than the reentrant jet type, which is prevalent at higher Froude numbers. The rate at which vapor/gas can be entrained by the counter-rotating vortex closure is much higher than for the reentrant jet closure (Brennen 1969).…”
Section: Cavity Closurementioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, the air flow rate of a ventilated cavity has often been measured instead, under the assumption that the flow rate necessary to maintain a certain length of cavity should be same for a vapor cavity and a ventilated cavity. (Brennen, 1969;Billet and Weir, 1975).…”
Section: Estimation Of Cavity Generation Ratementioning
confidence: 99%